KEDWIBAHASAAN PADA NOVEL LOVE SPARKS IN KOREA KARYA ASMA NADIA DAN IMPLIKASINYA TERHADAP PEMBELAJARAN BAHASA INDONESIA DI SMA - Putri, Shintya Anggun Kencana; Mulyati, Sri; Sari, Vita Ika (Basastra: Jurnal Bahasa, Sastra, dan Pengajarannya, 2020)
This study aims to describe: (1) the bilingualism of the novel Love Sparks In Korea by Asma Nadia; (2) describe the implications of bilingual learning in the novel Love Sparks In Korea by Asma Nadia. This study uses a sociolinguistic study with a sociological approach, the data source comes from the novel Love Sparks In Korea by Asma Nadia, the data form in the form of speech fragments. Data collection techniques using the method of reading with reading techniques. The technique of presenting the results of the data analysis used is informal technique. Based on the results of bilingual studies found in the novel Love Sparks In Korea by Asma Nadia, they consist of (1) compound bilingualness totaling 5 data: 11.4%, (2) coordinative bounty totaling 9 data: 20.4%, (3) subordinative bilingualism totaling 30 data: 68.2%. The results of this study can be used as a reference in language learning activities in high school. Through this learning students are expected to be able to understand the various languages used daily, and have a positive impact on future lives